Effective methods of teaching in media thinking and literacy lesson and providing practical solutions form teachers’ perspective - Pishbaz, Mohammad (2020)
Media literacy is a set of learnable skills that refers to the ability to access, analyze, and create a variety of media messages. Also, media literacy is an essential skill in today's world. To move into today's complex media environment, we should able to understand better media messages. People with media literacy will be able to discover the complex messages found in television, radio, newspapers, magazines, books, billboards, internet and other independent media. They can also create their own media and participate actively in shaping media culture. In this regard, the present study has identified a new book on "Media Thinking and Literacy" at secondary high schools, from the teachers' perspective, from the aspects of teaching methods including contexts, process, input and output. In this research, the type of research is an applied one, which is done by descriptive method and survey. The statistical population consisted of all teachers of 10th level of school in district 18 of Tehran and the sample size was determined using Morgan table. After survey from teachers, data analysis. The results with using One Sample T-Test indicated that the teaching methods of this book were in the medium to high, in terms of contexts, inputs, processes, and outputs. Also, the results of Friedman test show that the most important priority of teaching methods of this book was the contextual factors, and the least important factor is the inputs.